EVALUASI KESESUAIAN PERESEPAN OBAT DIARE ANAK BERDASARKAN MANAJEMEN TERPADU BALITA SAKIT KEMENKES 2022 DI KLINIK “X” KABUPATEN SIDOARJO - Andito, Didik; Sulistyowati, Emi; Priyoherianto, Andri; Puspadina, Valiandri (As-Syifaa Jurnal Farmasi, 2025)
Diarrhea is an incident of defecation with a consistency that is more liquid than usual, with a frequency of three or more times per day. Improper and rapid management is the main cause of death from diarrhea. The Ministry of Health has begun to disseminate the Guidelines for the Management of Sick Toddler Therapy (MTBS) 2022. This study aims to evaluate the suitability of prescribing children's diarrhea medications by the Ministry of Health MTBS 2022 guidelines in the outpatient unit of Clinic "X" in Sidoarjo Regency. This study uses a descriptive evaluative design of the pattern of prescribing children's diarrhea based on the 2022 Ministry of Health MTBS, which was conducted during July - December 2023. The population in this study was the medical records of pediatric patients with diarrhea. Samples collected using a simple random technique with specific inclusion and exclusion criteria. Data were taken from medical records, including gender, age, diagnosis, and type of medication prescribed, and analyzed to evaluate prescribing based on the 2022 Ministry of Health MTBS guidelines. The results of the prescribing pattern analysis showed a single prescribing pattern for 10 patients (16.67%) and a combination for 50 patients (83.33%). The appropriate prescribing pattern included a combination of ORS and zinc for 2 (3.33%) and inappropriate single without ORS and zinc, single only zinc or ORS, combination without zinc and ORS, and combination with only zinc or ORS respectively 8 (13.33%), 2 (3.33%), 19 (31.67%) and 29 (48.33%). Evaluation of prescribing patterns that did not comply with the guidelines revealed that 96.67% of prescriptions were made without including the administration of a combination of oral rehydration salt (ORS) and zinc, whereas those that complied with the guidelines included combinations that included the administration of a combination of oral rehydration salt (ORS) and zinc in 3.33% of cases